Migrant Remittance Patterns in South Africa: A Micro-Level Analysis - Sibindi, Athenia Bongani; Ngcobo, Lindiwe (Journal of Economics and Behavioral Studies, 2018)
Migrant remittances increasingly constitute a significant source of financial inflows into emerging markets. Hitherto, extant studies have focused nearly exclusively on the macroeconomic benefits of remittances. Such studies have documented that the top benefits that accrue to the receiving country of remittances include: savings mobilisation, fostering intermediation, investment, sustenance of families and the enabling of access to health care and education by households who ordinarily would not afford to pay for these services. This study departs from the norm and investigated the migrant remittance patterns from a micro-level perspective by focusing on South Africa which is one of the top twenty remittance receiving countries in the world. The South Africa-National Income Dynamics Study dataset was employed in this study. Firstly, this study established that remittances constitute a significant source of income for households in South Africa. Secondly, it was established that the remittance variable is positively related to the household income variable and the result was highly statistically significant. Thirdly, the results of this study confirmed that the level of remittances is dependent on the level of education of the household member, with the inclination of the highly educated migrant worker to send more money to support their household. The South African government should consider as a policy instrument encouraging migrant workers in the diaspora to remit more money back into the country through the facilitation of ease of access of financial services.